2019
DOI: 10.1523/jneurosci.1952-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of RAB-5 Increases EFF-1 Fusogen Availability at the Cell Surface and Promotes the Regenerative Axonal Fusion Capacity of the Neuron

Abstract: Following a transection injury to the axon, neurons from a number of species have the ability to undergo spontaneous repair via fusion of the two separated axonal fragments. In the nematode Caenorhabditis elegans, this highly efficient regenerative axonal fusion is mediated by epithelial fusion failure-1 (EFF-1), a fusogenic protein that functions at the membrane to merge the two axonal fragments. Identifying modulators of axonal fusion and EFF-1 is an important step toward a better understanding of this repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The effects of fusogen overexpression in neurons could go beyond neuronal cell−cell fusion and associated behavioral defects. In C. elegans, fission during endocytosis and phagocytosis can be mediated by AFF-1 and EFF-1, respectively (54,55), and EFF-1−mediated axonal fusion following injury has been shown to be regulated by the GTPase RAB-5 (56). It is therefore possible that the expression of fusogens in neurons can not only result in neuronal fusion but also impact on fission events that could affect neuronal morphology, repair, and function.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of fusogen overexpression in neurons could go beyond neuronal cell−cell fusion and associated behavioral defects. In C. elegans, fission during endocytosis and phagocytosis can be mediated by AFF-1 and EFF-1, respectively (54,55), and EFF-1−mediated axonal fusion following injury has been shown to be regulated by the GTPase RAB-5 (56). It is therefore possible that the expression of fusogens in neurons can not only result in neuronal fusion but also impact on fission events that could affect neuronal morphology, repair, and function.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules have been shown to control the presence of EFF-1 to fusion sites in larval hypodermal cells. In the context of axonal repair, we have previously shown that RAB-5 regulates fusion by controlling the levels of EFF-1 in C. elegans ( 19 ). There was a notable increase in the amount of EFF-1 with cotransfection of ADM-4 in HEK293T cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, EFF-1 transmembrane segments anchored in the two opposing membranes are brought into contact, pulling the two membranes into one ( 13 ). Previous studies have shown that monomeric EFF-1 is metastable ( 13 ) and that EFF-1 internalization from the cell membrane can prevent axonal fusion ( 19 ), whereas trimeric EFF-1 is stable and irreversible ( 13 ). However, the molecules that regulate the formation of functional EFF-1 trimers from EFF-1 monomers across opposing membranes to allow axonal fusion after injury remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The transparent body of C. elegans further allows analysis of such phenotypes, including axon regrowth rate, guidance, and fusion at a single neuron resolution in vivo with fluorescence microscopy. Past nerve regeneration studies in C. elegans have led to the discovery of many conserved nerve regeneration pathways [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] , notably the dual leucine zipper kinase (DLK-1/p38) signaling cascade, whose role in neural development, regeneration, and degeneration has been confirmed in numerous vertebrate and invertebrate species 7,[27][28][29][30][31] .…”
Section: Mainmentioning
confidence: 99%